Symptomatic Vocabulary in Magn Function - E. R. Ioanesyan (Научный диалог)
The article is devoted to the problem of marking the intensity of emotions in language. The main classes of lexical units that can act as indicators of strong emotions are briefly presented. The article includes the abbreviation Magn, which is the name of the corresponding lexical function in the model “Sense ↔ Text” (in the conception by Melchuk, 1974). Magn in this model is used “to denote ‘high degree,’ ‘intensity (≈ ‘very’) of the situation itself or its actants.” The main attention is paid to the symptomatic vocabulary, marking the intensity of emotion through reference to the subject of emotion. We have identified two classes of symptomatic units in the Magn function: (1) expressions that link the emotion and the state of a person in the power of that emotion, such as going crazy with anxiety , not remembering yourself with anger , beside yourself with joy ; (2) expressions that link the emotion and the reaction of a person to this emotion, for example, to become cold with fear , numb with horror , blush with pleasure , freeze with surprise , etc. The main object of study were symptomatic expressions of the French language, the material of Spanish, Italian, Portuguese, English and German languages was also involved. The study is based on a large corpus of explanatory and bilingual dictionaries, linguistic corpus data. The relevance of this study is determined by the interest of modern science to the study of emotions and their conceptualization in language, because emotions are one of the most complex systems of the inner world of a man, reflected in the linguistic picture of the world.